Keabsahan Jual Beli Tanah dan Rumah Menggunakan Surat Kuasa dengan Dibubuhi Cap Jempol yang Tidak Disahkan di Hadapan Notaris (Studi Putusan Mahkamah Agung Nomor 2513 K/Pdt/2018) - M. Permata Sakti; Hasim Purba; Maria Kaban (CV Rewang Rencang, 2025)
The practice of using power of attorney to sell in land sale and purchase transactions without notarial legalisation has given rise to complex legal problems because it harms the parties and creates legal uncertainty in the Indonesian land system. This study uses a normative juridical method. The results show that a power of attorney to sell affixed with a thumbprint without notarisation does not meet the formal requirements as stipulated in Article 1874 paragraph (2) of the Civil Code and Article 286 paragraph (2) of the RBg. Analysis of the legal considerations of the panel of judges in Supreme Court Decision Number 2513 K/ Pdt/2018 reveal fundamental weaknesses because they prioritise administrative aspects, thereby creating tension between the protection of bona fide buyers and substantive justice for landowners who are victims of power abuse.